The Effects of Identity and Political Consciousness on the Success and Failures of the Activist Group AIDS Coalition to Unleash Power (ACT-UP) - Milbrath, Ryan Michael (My University, 2009)
This paper will provide a comprehensive analysis of the social movement headed by the group AIDS Coalition to Unleash Power (ACT-UP). The ineffective governmental response to the AIDS epidemic of the early 1980s prompted the formation of an activist group dedicated to securing government intervention on behalf of AIDS victims, reforms for the production of AIDS treatment drugs, and challenging the underlying heterosexism found in political, economic and social structures. In my paper I will explain the material conditions that prompted the formation of ACT-UP, the use of artwork and direct action demonstrations to build consciousness in the gay community, and the negative effects of narrowing political consciousness. I will also discuss the impact of socio-economic and gay identity on the tactics of ACT-UP. Lastly, I will discuss the successes and failures of ACT-UP's primary objectives. In my paper, I am arguing that although ACT-UP successfully materialized their goals relating to AIDS treatment, research, and education, the movement dissolved in 1993 because of the organization's narrowed political consciousness and narrowed collective identity.
Keywords: Homophobia--Political aspects.; AIDS (Disease)--Political aspects.; Gays--Identity.; AIDS activists.; ACT UP (Organization)--History.